Systemic Thiol-Disulfide Homeostasis and Contemporaneous Menstrual Pain Intensity in Primary Dysmenorrhea: A Prospective Observational Study - Gonca Turker Engin; Mert Ishak Kaya; Duygu Tugrul Ersak; Ugurcan Zorlu; Raziye Toksoz; Elcin Islek Secen; Goktug Okyar; Salim Neselioglu (Gynecology Obstetrics & Reproductive Medicine, 2026)
OBJECTIVE: Primary dysmenorrhea (PD) is associated with prostaglandin-mediated uterine hypercontractility, transient ischemia, inflammation, and oxidative stress. Whether systemic redox biomarkers reflect menstrual pain intensity at a specific clinical time point remains uncertain. This study evaluated the associations of thiol-disulfide homeostasis parameters and ischemia-modified albumin (IMA) with contemporaneous menstrual pain intensity among women with PD. STUDY DESIGN: This prospective observational study included 98 women with PD. Pain intensity was assessed immediately before venous blood sampling during menstrual days 1-4 using a 10-cm Visual Analog Scale (VAS). The primary analysis examined continuous contemporaneous VAS scores. A secondary exploratory analysis classified pain as mild (>0 to 3), moderate (>3 to 6), severe (>6 to 8), or very severe (>8 to 10). Native thiol, total thiol, disulfide, thiol-disulfide ratios, and IMA were evaluated. RESULTS: Spearman correlation coefficients between contemporaneous VAS score and the measured biomarkers ranged from -0.10 to 0.10. All bootstrap 95% confidence intervals included zero, with outermost limits of approximately -0.29 and 0.29. Menstrual sampling-day-adjusted analyses and the sensitivity analysis using the retrospective worst-pain score yielded concordant findings. In the secondary categorical analysis, no significant differences were observed for native thiol (p=0.9913), total thiol (p=0.9805), disulfide (p=0.3098), the thiol-disulfide ratios (p=0.4704-0.5095), or ischemia-modified albumin (p=0.8986). All Holm-adjusted p values were 1.000. CONCLUSION: Systemic thiol-disulfide homeostasis parameters and unadjusted IMA were not associated with contemporaneous menstrual pain intensity in this cohort. A single systemic measurement may not adequately represent the localized, dynamic, and centrally modulated mechanisms underlying menstrual pain. Future studies are needed to improve diagnostic and therapeutic strategies for PD.